Human external ophthalmomyiasis caused by Lucilia sericata Meigen (Diptera: Calliphoridae) – a green bottle fly - Tanja Kalezic; Milenko Stojkovic; Ivana Vukovic; Radoslava Spasic; Marko Andjelkovic; Svetlana Stanojlovic; Marija Bozic; Aleksandar Dzamic (Journal of Infection in Developing Countries)
Ophthalmomyiasis externa is the result of infestation of the conjunctiva by the larval form or maggots of flies from the order Diptera. If not recognized and managed appropriately, it can be complicated by the potentially fatal condition ophthalmomyiasis interna. Ophthalmomyiasis externa is mainly caused by the sheep bot fly (Oestrus ovis). We present the first case, to our knowledge, of ophthalmomyiasis externa in an elderly woman from Belgrade caused by Lucilia sericata Meigen – a green bottle fly.